Mulibrey nanism and immunological complications: a comprehensive case report and literature review - Gazzin, Andrea; Pala, Francesca; Bosticardo, Marita; Niemela, Julie; Stoddard, Jennifer; Biasin, Eleonora; Quarello, Paola; Carli, Diana; Ferroni, Francesca; Delmonte, Ottavia M.; Montin, Davide; Rosenzweig, Sergio D.; et al. (Frontiers in Immunology, 2023)
Introduction: Mulibrey Nanism (MUL) is a rare disorder caused by TRIM37 gene variants characterized by growth failure, dysmorphic features, congestive heart failure (CHF) and an increased risk of Wilms' tumor. While immune system impairment has been documented in MUL, the underlying mechanisms remain poorly understood. Methods: We present a case of MUL with progressive lymphopenia and review similar cases from the literature.Results: Our patient presented with prenatal onset growth restriction, characteristic dysmorphic features and Wilms' tumor. She developed progressive lymphopenia starting at 10 years of age, leading to the initiation of intravenous immunoglobulin (IVIG) replacement therapy and infection prophylaxis.Genetic analysis detected a likely pathogenic variant on the maternal allele and copy number loss on the paternal allele in TRIM37. Subsequently a cardiac MRI was conducted revealing signs of pericardial constriction raising concerns for intestinal lymphatic losses. The cessation of IVIG therapy did not coincide with any increase in the rate of infections. The patient exhibited a distinct immunological profile, characterized by hypogammaglobulinemia, impaired antibody responses, and skewed T cell subsets with an altered CD4+/CD8+ ratio, consistent with previous reports. Normal thymocyte development assessed by artificial thymic organoid platform ruled out an early hematopoietic intrinsic defect of T cell development. Discussion: The immunological profile of MUL patients reported so far shares similarities with that described in Protein-Losing Enteropathy (PLE) secondary to CHF in Fontan circulation and Primary Intestinal Lymphangiectasia (PIL). These similarities include hypogammaglobulinemia, significant T cell deficiency with decreased CD4+ and CD8+ counts, altered CD4+/CD8+ ratios, and significantly modified CD4+ and CD8+ T cell phenotypes toward effector and terminal differentiated T cells, accompanied by a loss of naïve CD45RA+ T lymphocytes. In MUL, CHF is a cardinal feature, occurring in a significant proportion of patients and influencing prognosis. Signs of CHF or constrictive pericarditis have been evident in all the cases reported here and in all cases of MUL with documented immune dysfunction reported so far. These observations raise intriguing connections between these conditions. However, further investigation is warranted to in-depth define the immunological defect, providing valuable insights into the pathophysiology and treatment strategies for this condition.